Pengaruh integrated marketing communication terhadap brand equity PT Nufarm Indonesia di Belu - Dinni, Zuiyina Ayu; Zuliestiana, Dinda Amanda (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
Indonesia is an agricultural country with the highest absorption of agricultural labor compared to the working population. The high level of agriculture in Indonesia, coupled with the demand for pesticides, is indicated by the value of the world agricultural chemical market from 2018 to 2020 which continues to increase and is predicted to continue to increase until 2025. Currently, more and more pesticide products are registered in Indonesia. PT Nufarm Indonesia has carried out its integrated marketing communication (promotion mix) since 2011 in Belu, NTT to build brand equity in the midst of competition. This study aims to determine how much influence PT Nufarm Indonesia's integrated marketing communication has in building its brand equity. The method used in this research is quantitative with a questionnaire as a tool to collect data on 100 respondents. The criteria for respondents are Nufarm fostered farmers in Belu, NTT who have used Nufarm Indonesia products more than once. The data obtained will be analyzed using Structural Equation Models (SEM) with Smartpls software. The findings of this study are that there is a significant effect of each dimension of integrated marketing communication on all dimensions of brand equity.